In-School Parent Involvement in International Schools in Dubai: Barriers and Motivations - Derrane, Orla (2016)
The aim of this research is to investigate the views of parents and teachers in Dubai as to how parents should be involved in their children’s education. The research focusses specifically on in-school parent involvement in academic activities and the motivations and barriers that lead to such involvement or lack thereof. Teachers’ views of parent involvement and what they see as parents’ roles was investigated alongside parent views. There may often be contrasts between what parents and teachers believe and want in this regard and so an understanding of the views of both groups would be necessary to have a comprehensive understanding of the concept as a whole, as it is experienced in an international school setting in Dubai. Hornby and Lafaele (2011) highlight a lack of research with respect to the differing aspirations for parental involvement between teachers and parents. The means of investigating views of both parents and teachers was through semi-structured interviews. I interviewed five parents who were involved in an in-school parent reading programme, five parents who were not involved in the programme and five teachers. I also conducted a follow up survey of a larger number of parents based on my findings from the interviews.